2015
DOI: 10.15252/embj.201592042
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease‐causing proline substitutions lead to presenilin 1 aggregation and malfunction

Abstract: Do different neurodegenerative maladies emanate from the failure of a mutual protein folding mechanism? We have addressed this question by comparing mutational patterns that are linked to the manifestation of distinct neurodegenerative disorders and identified similar neurodegeneration-linked proline substitutions in the prion protein and in presenilin 1 that underlie the development of a prion disorder and of familial Alzheimer's disease (fAD), respectively. These substitutions were found to prevent the endop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 69 publications
0
29
0
Order By: Relevance
“…The association of aggresomes with neurodegenerative maladies was demonstrated by accumulation of the familial AD (fAD)-linked, mutated presenilin 1 (PS1) carrying the A246E mutation (PS1 is an active component of the g-secretase complex) in these structures (Johnston et al 1998). Interestingly, PS1 molecules that harbor other fAD-causing mutations accumulate within the ER upon proteasome inhibition (Ben-Gedalya et al 2015), showing that distinct conformers of the same protein can be sorted to distinct cellular deposition sites. Toxic PrP species (Kristiansen et al 2005), disease-causing PrP mutants (Cohen and Taraboulos 2003;Mishra et al 2003), and PD-associated, aggregated a-synuclein (Tanaka et al 2004;Wong et al 2008) were also shown to be deposited in aggresomes of mammalian cells, further linking these sites with human illnesses.…”
Section: Cellular Deposition Sitesmentioning
confidence: 99%
“…The association of aggresomes with neurodegenerative maladies was demonstrated by accumulation of the familial AD (fAD)-linked, mutated presenilin 1 (PS1) carrying the A246E mutation (PS1 is an active component of the g-secretase complex) in these structures (Johnston et al 1998). Interestingly, PS1 molecules that harbor other fAD-causing mutations accumulate within the ER upon proteasome inhibition (Ben-Gedalya et al 2015), showing that distinct conformers of the same protein can be sorted to distinct cellular deposition sites. Toxic PrP species (Kristiansen et al 2005), disease-causing PrP mutants (Cohen and Taraboulos 2003;Mishra et al 2003), and PD-associated, aggregated a-synuclein (Tanaka et al 2004;Wong et al 2008) were also shown to be deposited in aggresomes of mammalian cells, further linking these sites with human illnesses.…”
Section: Cellular Deposition Sitesmentioning
confidence: 99%
“…Recently, we discovered that familial AD-causing Proline substitutions in residues 264 or 267 in the sequence of presenilin 1 (PS1) abolish a cyclophilin recognition site, leading to PS1 misfolding and aggregation and to the development of certain cases of the disease (13). This study indicates that cyclophilins are key players in the maintenance of proteostasis and the prevention of neurodegeneration.…”
Section: Abstract: Neurodegeneration • Chaperones • Aggresome • Protmentioning
confidence: 99%
“…Hitherto, there has been no evidence that CsA treatment induces neurodegeneration; however, the use of CsA, an immunosuppressant that was prescribed for extended periods to individuals who underwent organ transplantations (41), should raise concern. This is particularly true because we previously found that the inhibition of cyclophilins appears to be involved in the development of certain cases of familial Alzheimer's disease (42). It is also possible that exosome secretions are increased in the later stages of life, enabling the spread of proteotoxicity and neurodegenerative disorders to manifest in an aging-associated manner [reviewed in Carvalhal Marques et al (43)].…”
Section: Prp-containing Exosomes and Prion Pathogenicitymentioning
confidence: 99%